An/archiving con/temporary dance/ing bodies - Panourgia, Marianna (Peripeti, 2024)
How is dance history written on bodies in classrooms in the 21st century? This paper derives from four years of ethnochoreological research in contemporary dance education within Higher Private Professional Dance Schools in Athens, Greece. Elaborating on the necessity of multimodal ways of capturing the process of corporeal transmission.